Determinants of in-hospital muscle loss in acute ischemic stroke – Results of the Muscle Assessment in Stroke Study (MASS). Issue 3 (March 2023) - Gungor, Levent; Arsava, Ethem Murat; Guler, Ayse; Togay Isikay, Canan; Aykac, Ozlem; Batur Caglayan, Hale Zeynep; Kozak, Hasan Huseyin; Aydingoz, Ustun; Topcuoglu, Mehmet Akif; ,; Akpinar, Erhan; Argin, Mehmet; et al.
Abstract : Background & aims: There is a change in the mass and composition of paretic and non-paretic skeletal muscles in the chronic phase of stroke. The multi-center, prospective, and observational Muscle Assessment in Stroke Study (MASS) was performed to evaluate the degree of muscle loss during the in-hospital acute stroke setting and determine factors contributing to this loss. Methods: Acute dysphagic ischemic stroke patients (n = 107) admitted to neuro-intensive care units were evaluated by computed tomography on days 1 and 14 after admission to determine the cross-sectional muscle area (CSMA) at the level of the mid-humerus, mid-thigh, and third lumbar vertebra. The percentage change in CSMA and variables associated with this change were evaluated by univariate and multivariate analyses. Results: There were significant reductions in CSMA in all the muscle groups analyzed; the most prominent change was observed in the arms (both: 14.2 ± 10.7%; paretic: 17.7 ± 11.6%; non-paretic: 10.1 ± 12.5%), followed by the muscles in the legs (both: 12.4 ± 8.7%; paretic: 12.9 ± 9.9%; non-paretic: 12.0 ± 9.3%) and L3-vertebra level (5.6 ± 9.8%) ( P < 0.001 for all). Higher calorie (r = −0.378, P < 0.001) or protein (r = −0.352, P < 0.001) intake was negatively associated with the decrease in CSMA of upper extremities. A substantial protein (≥0.4 g/kg/d) or calorie (≥5 kcal/kg/d) gap between targeted or actual intake was related to a larger decrease in CSMA in all the anatomic regions ( P ≤ 0.05 for all). Other significant predictors of muscle loss included history of diabetes mellitus, male sex, higher BMI, in-hospital infections, and the necessity for invasive mechanical ventilation. Conclusions: There is a considerable degree of loss in the global muscle mass in acute ischemic stroke patients over a two-week period. Along with several factors, falling significantly behind the daily protein or calorie targets was related to the decrease in the muscle area. Trial registration information: clinicaltrials.gov identifier NCT03825419. Graphical abstract: Image 1